إتجاهات معلمي الطور الابتدائي حول الدمج المدرسي للأطفال في وضعية إعاقة - ورخ, زكريا (University of Eloued جامعة الوادي, 2021)
الملـخص: هدفت الدراسة الى التعرف على اتجاهات معلمي الطور الابتدائي حول الدمج المدرسي للأطفال في وضعية إعاقة مع أقرانهم العاديين، ومعرفة مدى تقبلهم لعملية الدمج في ضوء المتغيرات(الجنس، الحالة الاجتماعية، وسنوات الخبرة)، ولتحقيق أهداف الدراسة استخدمنا المنهج الوصفي التحليلي، وقمنا بتطوير استبانة اشتملت على (45) فقرة موزعة على ثلاثة مجالات وهي، المجال الأول : خبرات المعلمين وتدريبهم، المجال الثاني : الاتجاهات نحو الظروف البيئية الداعمة لدمج ذوي الإعاقة، المجال الثالث : الاتجاهات نحو الجوانب الاجتماعية والنفسية في التعامل مع ذوي الإعاقة وأسرهم، وطبقت الدراسة على عينة عشوائية بلعت (100) معلم ومعلمة مثلت ما نسبته (%24) من مجتمع الدراسة البالغ (415) من معلمي المدارس الابتدائية ببلدية قمار، ولاية الوادي، وبعد عملية جمع الاستبانات، تم معالجتها إحصائيا باستخدام المتوسطات الحسابية والنسب المئوية والانحرافات المعيارية ومستوى الدلالة، توصلت الدراسة الى الدرجة الكلية لاستجابات المعلمين عن جميع فقرات الاستبانة إيجابية، حيث بلعت النسبة المئوية لاستجابات المبحوثين عن هذه الفقرات (63.84 %)، وعدم وجود فروق ذات دالة إحصائيا في اتجاهات المعلمين حول دمج التلاميذ في وضعية إعاقة مع أقرانهم في المدارس العادية تعزى لمتغيرات الجنس، والحالة الاجتماعية، وسنوات الخبرة، وفي ضوء هذه النتائج ومناقشتها، أوصينا بإجراء المزيد من الدراسات حول فلسفة الدمج، وإعداد المعلمين وتأهيلهم مسبقا لعملية الدمج، وتوفير غرف مصادر خاصة بالتلاميذ في وضعية إعاقة في المدارس، وزيادة الحوافز للمعلمين في مجال تعليم ذوي الإعاقة. Abstract : This study aims to examine primary stage teachers attitudes towards the integration of students with disabilities with their peers, and also to recognize the level of their acceptance of this integration process on the basis of some variable : (gender, martial status and years of experience). For achieving the study objectives, we used the analytical descriptive approach and we developed a questionnaire which included (45) paragraphs distributed into three fields. The first field : the experiences and training of teachers. The second field : the attitudes towards the environmental circumstances which support the integration of students with disabilities. The third field : the attitudes towards the social and psychological aspects of dealing with students with disabilities and their families. The study was applied to a startified random sample consists (100) male and female teachers representing (24%) of the study population which consists (415) of primary schools in Guemar, department of El-oued. After collecting questionnaires, they were statistically processes by using arithmetic means, percentages and standard deviations as well as level of significance. The study concluded that the total degree of teachers responses to all questionnaire paragraphs was positive ; as the percentage of participants responses to these paragraphs (63.84%) and there were no statistically significant differences in teachers attitudes towards the integration of student with disabilities with their peers in governmental schools to be attributed to the variables of gender, marital status and years of experience. Based on discussing these findings, we recommanded to carry out further, studies on the integration philosophy, preparing and qualifying teachers in advance to the integration process, providing special resource rooms in schools for students with disabilities, as well as increasing incentives for teachers working in education for students with disabilities.
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: اتجاهات المعلمين، الدمج المدرسي; Attitudes des enseignants, intégration scolaire; Teachers' attitudes, school integration